Segregação sócio-espacial na periferia metropolitana: uma análise do município de Guarulhos - Becceneri, Leandro Blanque [UNIFESP] (2010)
This paper addresses the socio-spatial segregation in the city of Guarulhos, the main objective is the identification of segregated areas by spatial analytical tools. Besides the conceptual discussion regarding the segregation, the paper intends to present strategies to identify segregated areas and a model of analysis capable of measuring the impact of segregation in different areas of the city, reflecting on the conditions of life of residents of the suburbs, being an issue always associated with segregation. Thus, besides a theoretical effort toward the consequences of segregation and its causes, this paper presents an empirical effort to draw up indicators to identify segregated areas and measure the impact that it has on the living conditions of the population, comprising also the areas of employment, income, education and residence time in the city.